The Properties and Concept of the Higher Education System in Uzbekistan - Filimonova, Liliya (Журнал иностранных языков и лингвистики, 2023)
New Uzbekistan education concept is being gradually changed. This year also will contribute in its development, as it got a motto of the year ‘Attention to the person and qualitative education’. Learners’ centered approach to it is education milestone. The quality of education depends on many factors, but firstly it should be defined as a system.